2018
DOI: 10.22610/jebs.v10i5(j).2518
|View full text |Cite
|
Sign up to set email alerts
|

Happiness Index for Human Resource Management Practitioners Associated with the Professional Body

Abstract: The study explored the perceptions of human resource management (HRM) practitioners in South Africa, using the following happiness dimensions: positive emotions, job-related wellbeing, affective commitment, employee engagement and distributive justice. The research approach was quantitative, and the research design was descriptive and longitudinal (i.e. over a two-year period). The convenience sampling technique was used to select participants. In 2016, the sample size was 204, and in 2017, the sample size was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The reason for the respondents to rate positive emotions as negative are that they were dissatisfied with their remuneration. The implication of this study for HR policymakers is that they must review their remuneration policy and practices and need to implement compensation management effectively and efficiently (Maleka et al, 2018). This implication ultimately implies that sound HRM in which compensation management is a major function leads employees to possess with positive emotions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the respondents to rate positive emotions as negative are that they were dissatisfied with their remuneration. The implication of this study for HR policymakers is that they must review their remuneration policy and practices and need to implement compensation management effectively and efficiently (Maleka et al, 2018). This implication ultimately implies that sound HRM in which compensation management is a major function leads employees to possess with positive emotions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…One of the major functions of HRM is compensation management which is consisted of pay management, incentive management and welfare management (Opatha, 2009). According to a longitudinal research done by Maleka, Swarts, and Mmako (2018) have found that participants have rated the positive emotions negatively, and they have rated the job-related wellbeing, affective commitment, employee engagement and distributive justice items positively. The dimensions of happiness index of which they have used are positive emotions, job-related wellbeing, affective commitment, employee engagement and distributive justice.…”
Section: Theoretical Frameworkmentioning
confidence: 99%